SOSIALISASI KESIAPAN UKS DALAM PENGEMBANGAN SISTEM KESEHATAN TERINTEGRASI IDENTIFIKASI PENYALAHGUNAAN NAPZA UNTUK MEWUJUDKAN REMAJA SEHAT - Made Wahyu Aditya; Luh Nova Dilisca Dwi Putri, Ni; Ketut Ayu Mirayanti , Ni; Agung Ngurah Putra Pradnyantara, Gusti (Jurnal Pengabdian Masyarakat Permata Indonesia, 2025)
Community service is the implementation of the practice of science, technology and arts and culture directly in the community. Health recording in schools must be carried out early in order to support healthy adolescents. The method used is to socialize the Readiness of UKS in developing an integrated health system for identifying drug abuse for 45 minutes each, followed by a demonstration of drug checking analysis with urine samples. The results of the socialization carried out, there was an increase in knowledge regarding medical recording in one healthy where there was a medical resume, students also knew the dangers of drugs that are currently vulnerable to school adolescents, the increase in knowledge was seen from the results of the pretest and posttest that had been carried out on 29 students with an age range of 15-18 years, the average pretest result was 6 and the posttest result was 10